2021
DOI: 10.1038/s41419-021-03816-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of extracellular vesicles in plasma reveals the characteristics and residual traces of COVID-19 patients without underlying diseases after 3 months of recovery

Abstract: More and more patients suffered from Coronavirus disease 2019 (COVID-19) have got recovery gradually due to suitable intervention. Increasing data mainly studies the clinical characteristics of recovered COVID-19 patients, and their molecular changes especially proteome changes also play the same important role in understanding of biological characteristics of recovered COVID-19 patients as clinical characteristics do. In our study, we reported the whole lung-ground glass-CT value-average of mild/severe recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…To further elaborate, we found enrichment of the complement proteins properdin, C1r, C5, C1q, C1QB, C4BPB, C4BPA, and C8A in the ChipEXO compared with exosomes from healthy donor plasma. Similar observations have been reported by Mao et al ( 22 ) and Sin Man Lam et al ( 47 ). Activation of the complement system is necessary to induce anti-SARS-CoV-2 immunity, yet it can also contribute to endothelial cell damage and multiorgan failure ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To further elaborate, we found enrichment of the complement proteins properdin, C1r, C5, C1q, C1QB, C4BPB, C4BPA, and C8A in the ChipEXO compared with exosomes from healthy donor plasma. Similar observations have been reported by Mao et al ( 22 ) and Sin Man Lam et al ( 47 ). Activation of the complement system is necessary to induce anti-SARS-CoV-2 immunity, yet it can also contribute to endothelial cell damage and multiorgan failure ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 91%
“…Through protein and RNA cargo, exosomes can convey information to distant remote cells upon uptake by endocytosis. Elegant studies by Mao et al ( 22 ) showed that the size distribution of exosomes from patients with SARS-CoV-2 infection was similar (55 to 145 nm) but the protein content varied with infection severity. There have been experimental models to study the immunomodulatory ( 23 , 24 ), tropic ( 25 ), and antifibrotic ( 26 ) activities of plasma-derived exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from studied soluble immune factors like antibodies and cytokines, EVs are emerging as novel and potent intercellular signalling mediators. EV cargos are under study as predictive tools for COVID‐19 severity (Balbi et al., 2021 ; Fujita et al., 2021 ; Mao et al., 2021 ). However, such recent studies required mass spectrometry and RNA‐seq of EVs cargo which is not easy to convert into routine clinical diagnostics due to the tedious processing and high expertise required.…”
Section: Discussionmentioning
confidence: 99%
“…EV cargos are under study as predictive tools for COVID-19 severity (Balbi et al, 2021;Fujita et al, 2021;Mao et al, 2021). However, such recent studies required mass spectrometry and RNA-seq of EVs cargo which is not easy to convert into routine clinical diagnostics due to the tedious processing and high expertise required.…”
Section:  Discussionmentioning
confidence: 99%
“…For patients in severe condition, international normalized ratio decreased during the process of recovery, while TBIL increased. 89 During the recovery, the outlier ratio of ALT, AST, and GGT remained high within the 14 days after discharge, but decreased significantly at 40 days after discharge. Meanwhile, the outlier ratio of ALP remained high during the follow-up period.…”
Section: Recovery Of Liver Dysfunctionmentioning
confidence: 87%